2021
DOI: 10.1073/pnas.2024852118
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated cerebrospinal fluid cytokine levels in tuberculous meningitis predict survival in response to dexamethasone

Abstract: Adjunctive treatment with antiinflammatory corticosteroids like dexamethasone increases survival in tuberculosis meningitis. Dexamethasone responsiveness associates with a C/T variant in Leukotriene A4 Hydrolase (LTA4H), which regulates expression of the proinflammatory mediator leukotriene B4 (LTB4). TT homozygotes, with increased expression of LTA4H, have the highest survival when treated with dexamethasone and the lowest survival without. While the T allele is present in only a minority of the world’s popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
(120 reference statements)
0
17
0
Order By: Relevance
“…We also recently showed that Tempol, a superoxide dismutase mimetic and potent antioxidant, improved antibiotic efficacy in a systemic S. aureus infection [6]. However, differences in host genetics may profoundly affect the success of immunomodulatory strategies [34].…”
Section: How Can We Improve Antibiotic Efficacy In Vivo?mentioning
confidence: 99%
“…We also recently showed that Tempol, a superoxide dismutase mimetic and potent antioxidant, improved antibiotic efficacy in a systemic S. aureus infection [6]. However, differences in host genetics may profoundly affect the success of immunomodulatory strategies [34].…”
Section: How Can We Improve Antibiotic Efficacy In Vivo?mentioning
confidence: 99%
“…These findings implicated LTB4 and TNF-induced inflammation in mortality ( 3 , 4 , 10 ). Moreover, high TNF levels were associated with mortality even among individuals without the high LTA4H-expressing variant suggesting that TNF excess, resulting from diverse host genetic determinants, is a far-reaching host susceptibility factor in TB ( 3 ). Consistent with these findings, necrotic human tuberculous granulomas have more TNF than non-necrotic ones ( 11 ).…”
mentioning
confidence: 92%
“…Tumor necrosis factor (TNF) is both a host resistance and susceptibility factor in tuberculosis (TB) ( 1 3 ). Findings in the genetically tractable and optically transparent zebrafish larva infected with Mycobacterium marinum (Mm) have revealed the mechanisms behind this dual effect ( 4 6 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of unbiased genetic screens and candidate gene approaches in zebrafish larvae has shed light on granuloma biology (Ramakrishnan, 2013; 2020). In particular, hypersusceptible zebrafish mutants displaying accelerated granuloma necrosis have identified innate immune host determinants that protect against necrosis and that are relevant in the context of human TB (Berg et al, 2016; Clay et al, 2008; Pagan et al, 2015; Roca and Ramakrishnan, 2013; Roca et al, 2019; Tobin et al, 2012; Tobin et al, 2010; Whitworth et al, 2021a; Whitworth et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%